Detection Small Aircraft by Acoustic Radiation (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2019)
Introduction. The problem of detecting small aircraft (SA) gave impetus to the creation of devices and systems for detecting different principles of operation. The detection of drones is complicated by their low visibility, both in the electromagnetic and acoustic ranges of the wavelengths and the feature of the flight path. Flight altitude can vary from units to tens of meters, and the dynamics of movement, from lagging to acceleration in an arbitrary direction. The use of radar allows detect drones in open areas at a distance of up to 1000m. Acoustic observation methods provide detection in complex terrain and the presence of green spaces. The detection range depends on the selected receiver, the radiation level of the object and the level of acoustic noise in the observation area. The development of the algorithm for calculating the detection range for the given detection characteristics seems to be relevant. Theoretical results. For the detection of flying objects it is proposed to use a receiver that provides non-coherent processing of acoustic signals - typical detection channel. The algorithm for calculating the maximum range of detection of SA is based on the statistical theory of detecting a noise-like signal disguised by interference. The algorithm for calculating the maximum detection range of SA is based on the statistical theory of detection of a noise-like signal. The sequence of calculating the maximum range of detection of LLA is reduced to establishing the type, effective frequency band and level of the radiation signal, determining the level of interference in the reception area, calculating the CW detection parameter, calculating the maximum detection range. Conclusions. To detect SA by acoustic radiation, it is proposed to use a detector according to the scheme of a typical detection channel. An algorithm for calculating the probability of detecting a noise signal is presented and a decision rule is established. The paper proposes an algorithm for calculating the maximum distance for detection of SA. An important factor in assessing the range is the distribution of air temperature with altitude and the direction of movement of air masses. Therefore, the algorithm should be improved taking into account the meteorological situation.